The Incompatibility of Motherhood and Professional Women's Football in England - Culvin, Alex; Bowes, Ali (Frontiers in Sports and Active Living, 2021)
There has been an advancement of professionalisation of women's football globally. Professional women's football in England has grown exponentially since the inception of the Football Association (FA) Women's Super League in 2011. This article offers an examination of the gender-specific needs of women as professional footballers, focusing specifically on the distinctive aspect of maternity policy. Sportswomen often feel compelled to make the difficult decision between motherhood and an athletic career. Contracts have become an essential component of the work-life of professional women footballers. However, these contracts pose questions regarding organisational intentions and motivations. This study draws on 30 semi-structured interviews with professional women footballers in England. Our key considerations include contracts, employment, motherhood, and athletes' bodies. This examination will develop our understanding of the complexities associated with professional football as a career choice for women.